2020
DOI: 10.1002/jia2.25466
|View full text |Cite
|
Sign up to set email alerts
|

I just believe there is a risk” understanding of undetectable equals untransmissible (U = U) among health providers and HIV‐negative partners in serodiscordant relationships in Kenya

Abstract: Introduction Sustained HIV viral suppression resulting from antiretroviral therapy (ART) eliminates the risk of HIV transmission, a concept popularly framed as Undetectable = Untransmittable (U = U). We explored knowledge and acceptance of information around the elimination of HIV transmission risk with ART (U = U) in Kenya. Methods Our qualitative study was conducted within a project evaluating the use of pre‐exposure prophylaxis (PrEP) integrated into ART care for HIV serodiscordant couples in public clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…Though most of the prevention benefits from U = U will be realized from an accurate understanding of U = U among PLHIV and those most vulnerable to HIV, we echo the need for a broader understanding as suggested by others [13]. Indeed, recent findings highlight how implicit and explicit stigma of healthcare professionals towards PLHIV may be a key driver of the lack of U = U communication [8,9]. HIV-related stigma negatively impacts HIV prevention and treatment [8,17], and, more generally, stigma has been proposed as fundamental cause of health inequality [20].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Though most of the prevention benefits from U = U will be realized from an accurate understanding of U = U among PLHIV and those most vulnerable to HIV, we echo the need for a broader understanding as suggested by others [13]. Indeed, recent findings highlight how implicit and explicit stigma of healthcare professionals towards PLHIV may be a key driver of the lack of U = U communication [8,9]. HIV-related stigma negatively impacts HIV prevention and treatment [8,17], and, more generally, stigma has been proposed as fundamental cause of health inequality [20].…”
Section: Resultsmentioning
confidence: 57%
“…In the interim, studies have shown that the slogan U = U, has not been clearly communicated by health providers in clinical care [8]. A qualitative study conducted in Kenya of HIV serodiscordant couples attending public clinics, showed how healthcare providers lacked "in-depth knowledge and conviction" on U = U [9]. Similarly, studies conducted in high-income settings (Canada [10,11], Italy [12], Australia [13] and the United States [14][15][16]), mostly on gay, bisexual and other men who have sex with men, have reported low awareness, understanding, belief or perceived accuracy of TasP or U = U, depending on the study.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA countries, the U = U campaign/slogan is gradually being integrated into HIV prevention promotion, although a more vigorous campaign strategy is needed. For PLWHIV, sustained viral suppression with a VL of <200 copies/mL, plus adherence to ART can lead to the maintenance of VLs and zero transmission [ 80 ]. Promoting strategies for U = U in SSA countries needs better communication and behavioral commitments [ 81 ] ( Box 2 ).…”
Section: Promoting U = U In Sub-saharan Africa and The Consequencementioning
confidence: 99%
“…Future studies should assess this strategy in routine clinical settings with clear messaging about prevention-effective adherence and U=U, particularly among young PrEP users. The influence of more readily available viral load testing (e.g., with point-of-care technology [ 38 ] will also be important to explore. Counseling about this strategy should consider the factors that were associated with more or less PrEP use than expected.…”
Section: Discussionmentioning
confidence: 99%